Integration of Jasmonic Acid and Ethylene Into Auxin Signaling in Root Development - Xu, Ping; Zhao, Ping-Xia; Cai, Xiao-Teng; Mao, Jie-Li; Miao, Zi-Qing; Xiang, Cheng-Bin (Frontiers in Plant Science, 2020)
As sessile organisms, plants must be highly adaptable to the changing environment by modifying their growth and development. Plants rely on their underground part, the root system, to absorb water and nutrients and to anchor to the ground. The root is a highly dynamic organ of indeterminate growth with new tissues produced by root stem cells. Plants have evolved unique molecular mechanisms to fine-tune root developmental processes, during which phytohormones play vital roles. These hormones often relay environmental signals to auxin signaling that ultimately directs root development programs. Therefore, the crosstalk among hormones is critical in the root development. In this review, we will focus on the recent progresses that jasmonic acid (JA) and ethylene signaling are integrated into auxin in regulating root development of Arabidopsis thaliana and discuss the key roles of transcription factors (TFs) ethylene response factors (ERFs) and homeobox proteins in the crosstalk.